From Farm to Fork: Growing a Scottish Food System That Doesn't Cost the Planet - Reay, Dave S.; Warnatzsch, Erika A.; Craig, Ed; Dawson, Lorna; George, Sheila; Norman, Rachel; Ritchie, Pete (Frontiers in Sustainable Food Systems, 2020)
Our global food system is under immense pressure. Feeding a growing human population well while simultaneously delivering required climate, biodiversity and other key outcomes arguably represents the biggest challenge of our civilization in the twenty-first century. Here we discuss this growing challenge in the context of Scotland, its progress to date, its new target of “net zero” greenhouse gas emissions by 2045, and its potential to be an exemplar for well-integrated land use policy that delivers on multiple aims. We highlight the role of research in informing rural policy and landowner actions and stress the importance of social science in helping to ensure a sustainable net zero transition that takes full account of socioeconomic contexts and avoids the big potential pitfalls of ignoring local contexts.